Urban Sprawl Analysis of Stratford in London, UK - Shava Shirwan Ibrahim Agha 1, a, * (Sulaimani Journal for Engineering Sciences)
Urban sprawl challenges London; its unchecked outward expansion complexly impacts the city. This research examines sprawl's historical and modern drivers in the UK's capital, gaining insights from Stratford in East London. We investigate sprawl's spatial patterns and ramifications in London by analyzing surveys, documents, and records. Providing a comprehensive explanation of Stratford's transformation from an industrial wasteland into an example of sprawl's dynamics, highlighting interconnections between housing markets, transportation infrastructure, and environmental issues. It is strongly promoted by global and local policies due to its positive outcomes in terms of contributing to the economic, environmental, and social goals of sustainability. Stratford's development reveals sprawl's benefits, like economic growth and issues like inequality. Outlining a microcosm of multifaceted dilemmas, Stratford crystallizes visible sprawl concerns. Learning from Stratford, we propose strategies for managing London's sprawl, including compact development, sustainable transportation infrastructure, and community-oriented planning. The aim is to expand and understanding of London's urban sprawl also provide insights to guide policies for a sustainable, equitable future. Urban sprawl poses complex challenges for London, requiring nuanced examination.